ANTIDIARRHOEAL ACTIVITY OF LEAF EXTRACT OF CELOSIA ARGENTEA IN EXPERIMENTALLY INDUCED DIARRHOEA IN RATS - Santosh Ghule; Sunder Singh; Gali Vidyasagar; Praveen Sharma; Bimlesh Kumar (Wolters Kluwer Medknow Publications, 2010)
In order to scientifically apprise some of the anecdotal, folkloric, ethno medicaluses of celosia argentea, the present study was undertaken to examine the antidiarrhoealproperties of alcoholic extract of leaves of Celosia argentea on diarrhoea by usingdifferent experimental models. Anti-diarrhoeal effect was evaluated by castor oil induceddiarrhoea, charcoal meal test and PGE2 induced diarrhoea. Loperamide (2 mg/kg) andatropine (0.1mg/kg) were used as standard drugs. Extract was used in 100 and 200 mg/kgdose. It produced dose related anti-diarrhoeal effect. Results suggest that it may actcentrally and may inhibit the PGE2 to give anti-diarrhoeal effects. Result of charcoal mealtest also suggests its anti-muscarinic activity.